Communication of the organization - Wojciech Słomski (Contemporary Economics, 2008)
Communication always takes place by means of symbols. Information must be coded by the sender, i.e. expressed by the use of symbols (mostly language symbols), and then decoded by the recipient. The process of message decoding may be divided into two stages: the acquisition and the interpretation of the message, so-called understanding through the attaching of the meaning to symbols, which made up the message. Itself the understanding of the message is a not a sufficient condition of communication, as it may happen so, that the recipient interprets (understands) the message in a more or less different way from what the sender intended to transfer, what in practice may lead to the consequences more or less similar to the total impossibility of decoding the message. We may speak about communication only if the meanings attached by the sender to the individual symbols are close or identical to the meanings attached to these symbols by the recipient.
Keywords: 330